2011
DOI: 10.1017/jfm.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional stability of vortex arrays in a stratified and rotating fluid

Abstract: International audienceThis paper investigates numerically and through an asymptotic approach the three-dimensional stability of steady vertical vortex arrays in a stratified and rotating fluid. Three classical vortex arrays are studied: the Kármán vortex street, the symmetric double row and the single row of co-rotating vortices. The asymptotic analysis assumes well-separated vortices and long-wavelength bending perturbations following Billant (J. Fluid Mech., vol. 660, 2010, p. 354) and Robinson & Saffman (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…However, † Email address for correspondence: eunok@ladhyx.polytechnique.fr many studies have shown that vortices have a pancake or lenticular shape in stratified fluids rather than being columnar. For example, interacting columnar vortices are unstable to zigzag instability (Billant & Chomaz 2000;Otheguy, Chomaz & Billant 2006;Billant 2010;Billant et al 2010;Deloncle, Billant & Chomaz 2011) and evolve into pancake vortices with a small aspect ratio. Coherent vortices generated from wakes or turbulence in stratified fluids also have a pancake shape (Lin, Boyer & Fernando 1992;Chomaz et al 1993;Fincham, Maxworthy & Spedding 1996;Spedding, Browand & Fincham 1996;Bonnier, Eiff & Bonneton 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, † Email address for correspondence: eunok@ladhyx.polytechnique.fr many studies have shown that vortices have a pancake or lenticular shape in stratified fluids rather than being columnar. For example, interacting columnar vortices are unstable to zigzag instability (Billant & Chomaz 2000;Otheguy, Chomaz & Billant 2006;Billant 2010;Billant et al 2010;Deloncle, Billant & Chomaz 2011) and evolve into pancake vortices with a small aspect ratio. Coherent vortices generated from wakes or turbulence in stratified fluids also have a pancake shape (Lin, Boyer & Fernando 1992;Chomaz et al 1993;Fincham, Maxworthy & Spedding 1996;Spedding, Browand & Fincham 1996;Bonnier, Eiff & Bonneton 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Layers can arise spontaneously through an instability, the zigzag instability, when several vertical vortices are interacting. This has been shown in the cases of pairs of counter-or co-rotating vortices (Billant & Chomaz 2000a;Otheguy, Chomaz & Billant 2006) and vortex arrays (Deloncle, Billant & Chomaz 2011). The study of such elementary flows is convenient to identify and understand some of the fundamental mechanisms at work in more complicated flows such as stratified turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…However, the small dimensions of the tank used in the experiments do not allow study of very small Froude numbers; it would require large cylinder diameters, which would reduce the aspect ratio below 10, leading to strong end effects. It is thus unclear what other instabilities would appear for very small Froude numbers (F < 0.1) where a zigzag instability might be observed (Deloncle, Billant & Chomaz 2011). We have tried to visualize the zigzag instability using larger cylinder diameters but it has not been observed with this experiment probably due to the small dimensions on the tank for that range of diameters (D > 32 mm).…”
Section: Stability Diagrammentioning
confidence: 91%